A Multi-path Droplet Routing Protocol for Digital Microfluidic Biochip - Swain, Jyotiranjan; Pyne, Sumanta (Informatica, 2024)
Droplet routing is a crucial phase in biochemical synthesis using a digital microfluidic biochip. The goal is to transport droplets from one module to another, maintaining fluidic constraints at every instant. This paper proposed a new droplet routing based on the MMSPED routing protocol. It uses multiple copies of route request packets to explore and discover the routes. To validate these routes, hello packets are used. The routes are then classified and sorted based on user-defined heuristics. Finally, route compaction is performed to generate the parallel moving sequence. The simulation result shows a 12.25% and 20.5% improvement in the latest arrival time for free and virtual topology, respectively.